Hematopoietic stem cells for cancer immunotherapy. Issue 1 (January 2014) - Gschweng, Eric; De Oliveira, Satiro; Kohn, Donald B.
Summary: Hematopoietic stem cells (HSCs) provide an attractive target for immunotherapy of cancer and leukemia by the introduction of genes encoding T‐cell receptors (TCRs) or chimeric antigen receptors (CARs) directed against tumor‐associated antigens. HSCs engraft for long‐term blood cell production and could provide a continuous source of targeted anti‐cancer effector cells to sustain remissions. T cells produced de novo from HSCs may continuously replenish anti‐tumor T cells that have become anergic or exhausted from ex vivo expansion or exposure to the intratumoral microenvironment. In addition, transgenic T cells produced in vivo undergo allelic exclusion, preventing co‐expression of an endogenous TCR that could mis‐pair with the introduced TCR chains and blunt activity or even cause off‐target reactivity. CAR‐engineered HSCs may produce myeloid and natural killer cells in addition to T cells expressing the CAR, providing broader anti‐tumor activity that arises quickly after transplant and does not solely require de novo thymopoiesis. Use of TCR‐ or CAR‐engineered HSCs would likely require cytoreductive conditioning to achieve long‐term engraftment, and this approach may be used in clinical settings where autologous HSC transplant is being performed to add a graft‐versus‐tumor effect. Results of experimental and preclinical studies performed to date are reviewed.